RhWRKY33 Positively Regulates Onset of Floral Senescence by Responding to Wounding- and Ethylene-Signaling in Rose Plants - Jing, Weikun; Zhao, Qingcui; Zhang, Shuai; Zeng, Daxing; Xu, Jiehua; Zhou, Hougao; Wang, Fenglan; Liu, Yang; Li, Yonghong (Frontiers in Plant Science, 2021)
Rose plants are one of the most important horticultural crops, whose commercial value mainly depends on long-distance transportation, and wounding and ethylene are the main factors leading to their quality decline and accelerated senescence in the process. However, underlying molecular mechanisms of crosstalk between wounding and ethylene in the regulation of flower senescence remain poorly understood. In relation to this, transcriptome analysis was performed on rose flowers subjected to various treatments, including control, wounding, ethylene, and wounding- and ethylene- (EW) dual treatment. A large number of differentially expressed genes (DEGs) were identified, ranging from 2,442 between the ethylene- and control-treated groups to 4,055 between the EW- and control-treated groups. Using weighted gene co-expression network analysis (WGCNA), we identified a hub gene RhWRKY33 (rchiobhmchr5g0071811), accumulated in the nucleus, where it may function as a transcription factor. Moreover, quantitative reverse transcription PCR (RT-qPCR) results showed that the expression of RhWRKY33 was higher in the wounding-, ethylene, and EW-treated petals than in the control-treated petals. We also functionally characterized the RhWRKY33 gene through virus-induced gene silencing (VIGS). The silencing of RhWRKY33 significantly delayed the senescence process in the different treatments (control, wounding, ethylene, and EW). Meanwhile, we found that the effect of RhWRKY33-silenced petals under ethylene and EW dual-treatment were stronger than those under wounding treatment in delaying the petal senescence process, implying that RhWRKY33 is closely involved with ethylene and wounding mediated petal senescence. Overall, the results indicate that RhWRKY33 positively regulates the onset of floral senescence mediated by both ethylene and wounding signaling, but relies heavily on ethylene signaling.